Introducing Oil and Gas to a Remote, Iconic Tourism Destination: Impacts on Broome and the West Kimberley - Hughes, Michael Phillip (Springer, 2014)
This chapter reviews the conflict relating to the proposed industrialisation of a remote and relatively pristine tourism region. The West Kimberley region is located in the remote North West of Western Australia with Broome as the regional center. Vibrant culture together with expansive remote wilderness, including rugged landscapes and pristine coastal and marine areas, provide the central components of an iconic nature-based and cultural tourism destination. While a proposal to develop a large-scale onshore oil and gas processing complex on the coast north of Broome has been withdrawn, questions remain about the environmental, social and cultural consequences of such development on a pre-existing tourism industry. The evidence indicates that the development would have significantly impacted on the region, potentially changing its image as a place to live and visit. Benefits to the region from the development would likely be relatively limited. The evidence relating to the relative merits of each sector are presented and discussed.